Penerapan Program Reflective Activity Pada Masa Pandemi Covid-19 - Roma Wijaya; Tsabit Bisma Yunas (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
SD Tumbuh 1 educators have a reflective activity program through the Class dojo application which aims to see students' academic and non-academic developments during class learning. Program implementation is carried out online and offline. This study aims to reveal the application of reflective activity programs during the COVID-19 pandemic carried out by educators for students. This research is a field research type qualitative research with the type of data used is the phenomenon. This research is descriptive in nature and uses a phenomenological approach with descriptive-analytical analysis. This research was conducted using a qualitative approach. Data collection was carried out using semi-structured interviews involving four participants consisting of two educators and two students. The results showed that educators and students preferred reflection activities to be carried out offline rather than online because students' attitudes and behavior could be observed more directly and students could choose the desired point category. During the reflection process, new problems arose, such as student dishonesty regarding their attitudes and behavior, students tended to look for value rather than interpret reflection activities.